Estudio de prefactibilidad para determinar la viabilidad de la instalación de una planta productora de desinfectantes en Trujillo - Colchao Perez, Rut Adela (2023)
The purpose of this report is to demonstrate the feasibility of installing a pine disinfectant production plant through a market, technical and economic study. This project seeks at a social level, to reduce the high unemployment rates in our country, and in a cultural economic sense, this study is relevant since the consumption of disinfectants has a significant demand. And the design used in this research is non-experimental - cross-sectional descriptive. The project began with a market study that was carried out in the province of Trujillo in order to estimate supply and demand. In this way, the unsatisfied demand in the market was projected and a target demand of 420,119 liters for the first year was determined. To achieve this, product differentiation was used as a competitive advantage, since it is aimed at distributors and wineries looking for a good quality product at a fair price. In addition, as a value proposition, the production process was innovated using management software and hardware tools for process automation. Then, the optimal location for the installation of the plant was sought and a technical study was also carried out to determine the capacities in requirements and process of raw material, supplies, materials, equipment, direct and indirect personnel, among others and the analysis of the impact environment, it was determined that the project would not have a negative impact on the environment. Afterwards, an economic and financial evaluation of the project was carried out, and a total investment of S/ 2,079,565 was determined, a VANE of S/ 3,873,382, an EIRR of 43%, a B/C E of S/ 2.86 and a PRI E of 3 years 5 months and 24 days. In the same way, the financial indicators were evaluated and a VANF of S/ 4,299,801, an IRR of 53%, a B/C F of S/ 4.45 and a PRI F of 3 years 3 months and 17 days were determined. On the other hand, regarding the sensitivity and risk analysis, it was determined that the project is economically and financially viable; because, considering the optimistic and pessimistic scenarios, the project continues to be profitable with a probability of 95% according to the variation of its sale price, variable cost, demand, COK and WACC. Finally, the economic and financial viability of the project was concluded.